PARTICULARITIES REGARDING THE OPERATING PROCESS OF THE CUTTING AND EXTRACTION DEVICE IN THE CANDU HORIZONTAL FUEL CHANNELS PRESSURE TUBE DECOMMISSIONING PART II: CUTTING AND EXTRACTING PRESSURE TUBE PROCESS - Constantin POPESCU; Gabi ROSCA FARTAT; Nicolae PANA; Tudor BURLAN-ROTAR; Constantin D.STANESCU; Doina ENE (Fiabilitate şi Durabilitate)
This paper presents some details of operation process for a Cutting and Extraction Device (CED) in order to achieve the decommissioning of the horizontal fuel channels pressure tube in the CANDU 6 nuclear reactor. The most important characteristic of the Cutting and Extraction Device (CED) is his capability of totally operator’s protection against the nuclear radiation during pressure tube decommissioning. The cutting and extracting pressure tube processes present few particularities due to special adopted technical solutions: a special module with three cutting rollers (system driven by an actuator), a guiding-extracting and connecting module (three fixing claws which are piloted by an actuator and block the device in the connecting position with extracting plugs). The Cutting and Extraction Device (CED) is a train of modules equipped with special systems to be fully automated, connected with a Programmable Logic Controller (PLC) and controlled by an operator panel type Human Machine Interface (HMI). All processes are monitored by video cameras. In case of error, the process is automatically stopped, the operator receiving an error message and the last sequence could be reinitialized or aborted due to safety reasons.